2019
DOI: 10.1016/j.jplph.2019.153001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating stress responses in cowpea under drought stress

Abstract: A B S T R A C TDrought impact on plants is an increasing concern under the climate change scenario. Cowpea (Vigna unguiculata L. Walp.) is considered as one of the most tolerant legume crops to drought, being the search for the best welladapted genotypes crucial to face the future challenges. Different approaches have been used for differentiating plant responses to drought stress. Plants of four cowpea genotypes were submitted to three watering regimens (a severe and moderate drought stress, and well-watered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 63 publications
(106 reference statements)
2
38
0
Order By: Relevance
“…Several studies have shown that soil moisture controls CO2 assimilation through its impact on stomatal conductance (Carvalho et al 2019;Munjonji et al 2017;Rivas et al 2016;Tankari et al 2019;Zhang et al 2013). Under unlimited soil moisture, leaf CO2 assimilation is high due to a higher stomatal conductance with the reverse being true for limited water supply.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that soil moisture controls CO2 assimilation through its impact on stomatal conductance (Carvalho et al 2019;Munjonji et al 2017;Rivas et al 2016;Tankari et al 2019;Zhang et al 2013). Under unlimited soil moisture, leaf CO2 assimilation is high due to a higher stomatal conductance with the reverse being true for limited water supply.…”
Section: Introductionmentioning
confidence: 99%
“…A severe lack of water damages the structure of chloroplast lamellae and lowers the chlorophyll content of plant leaves. Accordingly, the chlorophyll content may be a useful indicator of plant sensitivity to drought stress (Dong et al 2019, Carvalho et al 2019. In this study, we observed that drought stress decreased the chlorophyll content considerably more in the wild type than in the PgMYB4-overexpressing Arabidopsis, which indicates a more substantial drought tolerance of the transgenic plants.…”
Section: Discussionmentioning
confidence: 53%
“…Changes in enzymatic activities under multiple stress conditions, such as water deficit and high temperature, as observed in the present study, may be associated with the activation of oxidative defense mechanisms of plants (Mansoor;Naqvi, 2013). The higher activity of antioxidant enzymes can contribute to a better tolerance to water deficit, thus justifying greater enzymatic activities in plants subjected to water stress, such as the activity of enzymes responsible for maintaining oxidative homeostasis in cowpea (Carvalho et al, 2019). For plants that were subjected to reduction in water availability in the vegetative and flowering stages, it can be noted that, in general, the lower the water availability, the greater the specific activity of SOD (first line of defense), as well as the enzymes that act in the second line of defense against oxidative stress (CAT, APX and GPX).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors consider this legume as a species with greater tolerance to water stress compared to other crops (Ndiso et al, 2016;Merwad;Desoky;Rady, 2018). These characteristics make cowpea cultivation relevant for food security, especially in the face of global climate change (Carvalho et al, 2019). Although this crop is adapted to semiarid conditions, water deficit and high temperatures during its development cycle can have a negative impact on production (Ndiso et al, 2016).…”
Section: Introductionmentioning
confidence: 99%